Developing Students’ Motivation at MTS Negeri Papi Enrekang in Speaking English through Selected Games - Umiyati Jabri (Universitas Muhammadiyah Enrekang, 2018)
This research aimed at finding whether the students were motivated to speak English by using communication games and also finding out students’ part. The sample consisted of 30 students in participation in the classroom. In this reaserch the data were obtained through questionnaire (one and two). The result of the questionnaire’s description showed that the motivation of students was positive. It can be concluded that students are motivated to learn English through communication games. It was proved from the findings the of the students’ averange score that was 89.6 and the mean score was 4.48. The level of motivation was considered very high based on Likert Scale, and the result of the Questionnaire preference showed that the students prefer jigsaw as communication games in speaking English with percentage, Jigsaw (56.7%), Giving Direction (33.3%), and Picture Pairs (10%).